2022
DOI: 10.1097/mcp.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

The role of PET in the management of sarcoidosis

Abstract: Purpose of reviewPET has emerged as method to determine the location and extent of disease activity in sarcoidosis. As most clinicians do not routinely utilize PET in the management of sarcoidosis, an understanding of the imaging technique is needed to comprehend the impact that PET abnormalities have on diagnosis, prognosis, and treatment.Recent findingsAlthough PET can detect inflammation because of sarcoidosis throughout the body, it is most often utilized for the diagnosis of cardiac sarcoidosis for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
8
0
2
Order By: Relevance
“…FDG-PET/CT is an important diagnostic tool in both thoracic and extra-thoracic sarcoidosis because of its ability to identify active inflammation [26 ▪▪ ]; however, it is still not indicated in standard work-up. Currently, it is mainly used to evaluate cardiac sarcoidosis and detect hidden extra-thoracic involvement in persistently symptomatic patients.…”
Section: Using Fdg-pet/computed Tomography In Sarcoidosis Managementmentioning
confidence: 99%
“…FDG-PET/CT is an important diagnostic tool in both thoracic and extra-thoracic sarcoidosis because of its ability to identify active inflammation [26 ▪▪ ]; however, it is still not indicated in standard work-up. Currently, it is mainly used to evaluate cardiac sarcoidosis and detect hidden extra-thoracic involvement in persistently symptomatic patients.…”
Section: Using Fdg-pet/computed Tomography In Sarcoidosis Managementmentioning
confidence: 99%
“…Apart from the accurate assessment of the cardiac structure and tissue characterization, cardiac MRI offers significant prognostic information for patients with suspected/known cardiac sarcoidosis [16 ▪▪ ,17,18]. Fluro-deoxy-glucose (FDG)-PET is an alternative advanced imaging modality used to identify myocardial (and body) inflammation and has a complementary role to cardiac MRI in the diagnostic pathway [19]. However, the selective use of these advanced imaging modalities at expert centres does not address the problem of screening, especially with regard to the presence of subclinical disease.…”
Section: Role Of Primary Care Physicians In Diagnosis Of Sarcoidosismentioning
confidence: 99%
“…In pulmonary sarcoidosis, FDG-PET/CT has exhibited a high sensitivity rate ranging between 94% and 100% in identification of ongoing inflammatory processes ( Figure 3 ) [ 60 , 61 ]. Few studies have investigated its diagnostic use in pulmonary sarcoidosis [ 62 , 63 , 64 ]. One retrospective study involving 95 patients, with 85% demonstrating signs of fibrotic disease, found that the severity of pulmonary involvement as assessed by HRCT and lung function parameters was associated with increased FDG uptake at a threshold standardized uptake value (SUVmax) of greater than or equal to 2.5 [ 63 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%